Large scale machine learning with Spark : discover everything you need to build robust machine learning applications with Spark 2.0 /: discover everything you need to build robust machine learning applications with Spark 2.0. (2016) - Karim, Md. Rezaul; Kaysar, Md. Mahedi
No abstract available